The silence of the lambs - Utt, Kenneth 1921-1994; Saxon, Edward; Bozman, Ron (Ronald M.); Tally, Ted; Demme, Jonathan 1944-; Foster, Jodie; Hopkins, Anthony 1937-; Glenn, Scott 1942-; Levine, Ted; Harris, Thomas 1940- (Columbia Tristar Home Video, 1991)
Young FBI agent Clarice Starling is assigned to help find a missing woman to save her from a psychopathic serial killer who skins his victims. Clarice attempts to gain a better insight into the twisted mind of the killer by talking to another psychopath Hannibal Lecter, who used to be a respected psychiatrist. FBI agent Jack Crawford believes that Lecter who is also a very powerful and clever mind manipulator have the answers to their questions to help locate the killer. Clarice must first try and gain Lecter's confidence before he is to give away any information.